Evaluating the Compliance of Official Vehicle usage and Security Procedures at BPKPD Office of West Sulawesi Province, Indonesia - Kartini, Kartini; Syukur, Abdul; Aisyah, St.; Wahid, Rivka Damayanti; Syam, Edy (Universitas Negeri Makassar, 2024)
The objective of this study is to examine the compliance of procedures for the use and security of official vehicles at the Regional Financial and Revenue Management Agency (BPKPD) of West Sulawesi Province in 2022 and 2023 with Permendagri No.19 of 2016. This can be observed in the procedures for the use and security of official vehicles as well as the completeness of the source documents. This study employs a descriptive qualitative research method. The findings demonstrate that BPKPD of West Sulawesi Province in 2022 and 2023 has implemented procedures for the use and security of official vehicles, accompanied by complete documentation. Consequently, the use and security of official vehicles at BPKPD of West Sulawesi Province in 2022 and 2023 are in compliance with Permendagri No.19 of 2016.